O efeito in vitro do extrato aquoso de erva mate (Ilex paraguariensis) na inflamação, estresse oxidativo e prevenção de sintomas parkinsonianos - Rosa, Tábada Samantha Marques (2018)
Parkinson's disease (PD) is a degenerative disease of the central nervous system, chronic and progressive. It is caused by an intense decrease in dopamine production. This disease is one of the main causes of neurological deficiency and its prevalence occurs worldwide, which justifies efforts to improve its treatment. The natural and low cost substances that can act to protect cells from oxidative stress, minimizing mitochondrial changes, inflammation and apoptosis, are strong candidates for the development of new therapeutic approaches of neuroprotection, in search of improvement and prevention of PD. Recent studies have revealed an inverse association between consumption of yerba mate and the risk of developing PD, other studies have also indicated an association between increased inflammatory response and PD. The present study was developed with the aqueous extract of yerba mate (Ilex paraguariensis), in vitro culture of SH-SY5Y and RAW 264.7 cells. The SH-SY5Y cells were pre-treated with mate and then exposed to rotenone, an in vitro PD inducer, for the analysis of the neuptrotoric effect of yerba mate on parkinsonian symptoms. And the RAW 264.7 cells, for the analysis, were pretreated with phytohemagglutinin and yerba mate, to check the inflammatory and oxidative markers. The research was carried out in the Laboratory of Biogenomics, Department of Morphology, Building 19, Campus of the Federal University of Santa Maria. Mitochondrial activity was decreased in the RAW 264.7 strain and increased in SH-SY5Y cells treated with an aqueous mate extract. Genotoxicity was not observed on exposure to the aqueous extract of mate in both cells. In apoptosis, RAW 264.7 showed an increase in caspase levels 1, 3 and 8 at the highest concentrations, but in SH-SY5Y cells there was an increase in caspases 1 and 8, only at high concentrations, and caspase 3 increased in all treatments. The data confirmed that treatment with Phytohemagglutinin induced a proliferative state and with maté an anti-inflammatory response. In SH-SY5Y cells, rotenone treatments decreased cell viability in a dose-dependent manner. When yerba mate exposure occurred before rotenone treatment, the tendency to apoptosis is attenuated, indicating a neuroprotective effect. It was concluded that in both cell lines the mate-herb, in general, presented anti-inflammatory effect. At the lowest concentrations, the neuroprotective effect was observed against rotenone damage in neuronal cells.